(untitled) (Proceedings of the International Conference on Future of Women, 2025)
The politics of gender and sexuality within political activism is a complex and contested field and words that resonate differently in different political and cultural contexts. influenced by interlocking identities, ideologies and interests. The place of women and LGBTQ+ people in, and their contribution to,gender rights activism has been empirically documented; however, little has been done to analyze how male activists think and act about gender and sexuality. One of them would be a bridge to that gap by the following studies: exploring the views of male activists from diverse ideological and activist contexts in North India.The study fills in that gap by exploring how North Indian male activists negotiate feminist and queer politics, framing the analysis around masculinity, male allyship, and intersectionality. Using focus groups discussion (FGDs), in-depth interviews and field observations, it investigates how caste, religion, political ideology, and activist location impact male participation in gender justice struggles. Results demonstrate a continuum of engagement—from actively questioning and challenging patriarchy through practice to upholding hierarchical forms of masculinity even within progressive strands of mobilization. In analysing their motivations, paradoxes and ideological frictions, the article provides an account of the process through which masculinities are shaped and challenged in a field of political action, and what this involves for transformative feminist and queer politics.